Lipotoxicity as a Barrier for T Cell-Based Therapies - Romy Böttcher-Loschinski; Judit Rial Saborido; Martin Böttcher; Sascha Kahlfuss; Dimitrios Mougiakakos (Biomolecules, 2022)
Nowadays, T-cell-based approaches play an increasing role in cancer treatment. In particular, the use of (genetically engineered) T-cells has heralded a novel era for various diseases with previously poor outcomes. Concurrently, the relationship between the functional behavior of immune cells and their metabolic state, known as immunometabolism, has been found to be an important determinant for the success of immunotherapy. In this context, immune cell metabolism is not only controlled by the expression of transcription factors, enzymes and transport proteins but also by nutrient availability and the presence of intermediate metabolites. The lack of as well as an oversupply of nutrients can be detrimental and lead to cellular dysfunction and damage, potentially resulting in reduced metabolic fitness and/or cell death. This review focusses on the detrimental effects of excessive exposure of T cells to fatty acids, known as lipotoxicity, in the context of an altered lipid tumor microenvironment. Furthermore, implications of T cell-related lipotoxicity for immunotherapy will be discussed, as well as potential therapeutic approaches.